FAKTOR RISIKO KEKURANGAN ENERGI KRONIK (KEK) PADA REMAJA PUTRI DI SEKOLAH MENENGAH ATAS NEGERI (SMAN) KELURAHAN LEMBANG MAJENE - Wahdaniyah; Ningsi, Nurpatwa Wilda; Justyulfah; Febriyani, Nadia; Arina; Hasan, Khoerianty (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2025)
Currently, Indonesia is experiencing a triple burden malnutrition, on the one hand it is still experiencing the problem of malnutrition, but on the other hand there is obesity and an increase in the prevalence of nutrition-related diseases such as Chronic Energy Deficiency. The current condition of adolescents is more interested in consuming ready-to-eat food which causes a high rate of nutritional deficiency so that it can affect nutritional problems in adolescents. This study aims to determine the risk factors for chronic energy deficiency in adolescent girls in Majene district. The population in this study is adolescent girls. The sampling technique is purposive sampling and the type of research used is Cross Sectional. The statistical test to be used is chi-quare or fisher-exact. The results of this study stated that of the four variables studied, namely infectious diseases, knowledge, diet and physical activity, the only factor that has a relationship with the incidence of KEK is the dietary factor. Thus, to reduce the prevalence of SEZs in adolescents, it can be maximized in providing education related to healthy diets.